Vegetation and Soil Structure around Bagmati River near Sundarijal - Basaula, Raiendra (Himalayan Biodiversity, 2017)
Vegetation samples in the form of herbarium and soil samples were collected from three stations of Bagmati river near the sundarijal. Vegetations were identified in Central Department of Botany. Frequency and relative frequency, density and relative density, dominance and relative dominance, important value index and biomass production of ground vegetation were determined. Castanopsis tribuloides was found dominant tree species. Soil samples of different stations were analyzed for different physical and chemical characters. in laboratory of Nepal Agriculture Research Council (NARC), in Khumaltar. The soil of study area was found acidic in nature. All collected soil samples were investigated.